THE CONSTITUTION IN THE NEW EDITION: NEW APPROACHES AND NEW LAW PRACTICE (IN THE EXAMPLE OF HUMAN AND CITIZEN'S RIGHTS AND FREEDOMS GUARANTEES) (American Journal of Research in Humanities and Social Sciences, 2023)
This article explores the new edition of the constitution, focusing on innovative approaches and legal practices that enhance the guarantees of rights and freedoms for individuals and citizens. It delves into the importance of updating constitutional frameworks to adapt to societal changes and the evolving needs of the people. By examining the implementation of safeguards for human rights and citizenship, the article sheds light on how these provisions serve as a model for ensuring the protection and promotion of fundamental liberties in contemporary society.